«Preescolar na Casa»: from preparation for school to family education in rural Galicia (España) - Ferradás Blanco, Rodolfo Luis; Franco López, José Pablo (Historia y Memoria de la Educación, 2018)
Preescolar na Casa is the educational action organized among families of children from zero to six years in rural Galicia, in a disperse population. It is based on daily life and the family and social environment. The action, first organized and promoted by the Caritas of Galicia, was initially managed by Caritas Diocesana de Lugo and from 2001 on by the Fundación Preescolar na Casa. This paper presents its theoretical foundations and describes and analyzes its activities and achievements over the 35 years of its existence (1977-2012).